Interactive Learning Module Development Design for Electronic and Digital Engineering at Aviation Polytechnic - Mulyadi Nur; Fatmawati Sabur; Yuyun Suprapto; Djunaedi Djunaedi; Sukarman Sukarman (Universitas Negeri Malang, 2025)
Education is the gateway for anyone For accept knowledge in frame increase source Power man to be of better quality. To realize these goals, a lecturer/educator must have the skills to choose, use methods and carry out new innovations in creating an effective and efficient learning environment for students. R & D (Research & Development) research is research that is oriented to research, design, produce, test, the validity of the resulting product in the form of an interactive teaching module to improve understanding of the concept of electronic and digital engineering material with a development model developed by M. Alessi and Stanley R. Trollip, which consists of the stages of Planning , Design , and Development . Data collection techniques used in this study are questionnaires, tests, interviews and observations. Techniques analysis data for eligibility media use analysis data descriptive, where the analysis is carried out using the Score stages results evaluation questionnaire Which obtained from for expert (media And material), in the form of quantitative data that is changed into categories with a linkert scale. The results of the study are that the entire interactive teaching module device can be accessed via the link https://online.fliphtml5.com/emxux/sjxl/ . The results of the assessment two expert material to fourth aspect obtained average score 3.15 Which qualitatively categorized Very Worthy (X ≥ 3.0) and the results of the assessment by two media experts obtained a value of 3.28 the result in category very feasible (X ≥ 3.0)